Intersections between polyvictimisation and mental health among adolescents in five urban disadvantaged settings: the role of gender - Mphatso Kamndaya; Pedro T. Pisa; Matthew F. Chersich; Michele R. Decker; Adesola Olumide; Rajib Acharya; Yan Cheng; Heena Brahmbhatt; Sinead Delany-Moretlwe (BMC, 2017)
Abstract Background Polyvictimisation (PV) - exposure to violence across multiple contexts - causes considerable morbidity and mortality among adolescents. Despite high levels of violence in urban disadvantaged settings, gender differences in associations between PV and mental health have not been well established. Methods We analysed data from a survey with 2393 adolescents aged 15-19 years, recruited using respondent-driven sampling from urban disadvantaged settings in Baltimore (USA), Delhi (India), Ibadan (Nigeria), Johannesburg (South Africa) and Shanghai (China). PV was defined as exposure to two or more types of violence in the past 12 months with family, peers, in the community, or from intimate partners and non-partner sexual violence. Weighted logistic regression models are presented by gender to evaluate whether PV is associated with posttraumatic stress, depression, suicidal thoughts and perceived health status. Results PV was extremely common overall, but ranged widely, from 74.5% of boys and 82.0% of girls in Johannesburg, to 25.8 and 23.9% respectively in Shanghai. Community violence was the predominant violence type, affecting 72.8-93.7% across the sites. More than half of girls (53.7%) and 45.9% of boys had at least one adverse mental health outcome. Compared to those that did not report violence, boys exposed to PV had 11.4 higher odds of having a negative perception of health (95%CI adjusted OR = 2.45-53.2), whilst this figure was 2.58 times in girls (95%CI = 1.62-4.12). Among girls, PV was associated with suicidal thoughts (adjusted OR = 4.68; 95%CI = 2.29-9.54), posttraumatic stress (aOR = 4.53; 95%CI = 2.44-8.41) and depression (aOR = 2.65; 95%CI = 1.25-5.63). Among boys, an association was only detected between PV and depression (aOR = 1.82; 95%CI = 1.00-3.33). Conclusion The findings demonstrate that PV is common among both sexes in urban disadvantaged settings across the world, and that it is associated with poor mental health outcomes in girls, and with poor health status in both girls and boys. Clearly, prevention interventions are failing to address violence exposure across multiple contexts, but especially within community settings and in Johannesburg. Interventions are needed to identify adolescents exposed to PV and link them to care, with services targeting a range of mental health conditions among girls and perhaps focusing on depression among boys.